SOSIALISASI KESEHATAN LINGKUNGAN DAN PENGOLAHAN SAMPAH ORGANIK MENJADI EKOENZIM KKN PMD UNRAM DESA GUNUNG RAJAK - Darunnafis, Moh. Khazani; Lestari, Ira; Istiani, Ratna Ayu; Maulani, Yasmin; Aini, Zinnur; Syahputra, M. Aprilian; Falah, Fajrul; Al Gazali, Rifyal Ghaizi; Salma; Hartuti, Sugi; Suripto (Jurnal Wicara, 2025)
Gunung Rajak Village, Sakra Barat District, East Lombok Regency, has a population of 6,875 people with an area of ​​624 hectares. One of the main problems faced by this village is the low level of public awareness in managing organic waste, which causes environmental pollution and health risks. Based on the previous UNRAM KKN PMD report, this village produces around 3,322.5 kg of waste per day, with more than 60% of it being organic waste that has not been optimally managed. To overcome this problem, KKN PMD students from the University of Mataram held a socialization and training on processing organic waste into eco-enzymes, namely liquids from the fermentation of organic waste that can be used as natural cleaners and organic fertilizers. This activity took place on January 18, 2025 at SDN 01 Gunung Rajak, with the main target of 30 posyandu cadres, most of whom are housewives. The methods used included observation, Focus Group Discussion (FGD), interactive lectures, and direct practice of making eco-enzymes. From the evaluation results, 85% of participants understood the benefits of eco-enzyme, and 70% of them were committed to implementing this technique in their homes. In addition, the use of eco-enzyme is predicted to reduce at least 1,900 kg of organic waste per month, while saving household costs that were previously allocated for the purchase of chemical cleaners. The implementation of community-based waste processing is expected to be a sustainable solution for Gunung Rajak Village, creating a cleaner, healthier environment, and increasing public awareness of the importance of organic waste management.If implemented widely, this method could serve as a pilot model for other villages facing similar challenges in waste management.